IMPLEMENTASI LEGISLASI BENIH DALAM MENSUKSESKAN SWASEMBADA PANGAN - Valeriana Darwis (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2016)
Seed has an important role  to  increasing  the  productivity of  food crops and has has a lot of legislation issued by the government relating to seed. However, to date there are no known legislation from local government (PEMDA) on seed (specific location).  At the current stage, the existing local legislation on seed was based on the initial legislation from the central government especially Cultivation Act No. 12/1992 and Government Legislation No.44/1995. To date the most important institution based on  the  existing  legislation  on  seed  is  BPSBTPH  (Seed  Control  and  Certification Services  Agency  for  Food  Crops  and  Horticulture).  BPSBTPH  has  a  function  to control  and  be  responsible  in  seed  production,  from  procurement,  distribution  and trading  activities.  To  optimize  their  role  and  function  the  BPSBTPH  should:  (1) develop policy for agricultural enterprises or farmers who have been used un-labelled seed; (2) participate in supervising new seed products from other agencies; (3) more focus on supervising duties and less pressure on achieving target in production that was set by local government.